Primary yield and multitranche structure in securitization issues: Explicative factors. A review - Miguel A. Pe\~na-Cerezo; Arturo Rodríguez-Castellanos; Francisco J. Ibá\~nez-Hernández (European Research on Management and Business Economics (ERMBE), 2016)
The reasons for the strong rise in the securitization phenomenon up until the start of the “subprime crisis” need to be analysed. According to many authors, they mainly stem from its offering the possibility of generating fixed yield securities with the highest rating and a low risk premium, thanks to the issues being structured in differentiated bond series, so that certain series absorb most of the risk, thus facilitating the safer or “senior” tranches having a higher rating. Accordingly, this paper reviews the literature on the factors underlying the generation of differentiated tranches in this type of issues and regarding the determining factors ofthe yield offered by securitization issues. It concludes thatthe search for more complete markets, along with the reducing of problems associated to the moral hazard, are the main reasons for the multi-tranche structuring. And given the strong influence of the number of tranches on the yield offered by the issues, the paper likewise concludes that the multitranche structures has been an efficient tool to place securitization issues with more competitive yields. – – El fuerte desarrollo experimentado por la titulización hasta la “crisis subprime” y su empleo en la actualidad, requiere analizar sus causas. Y estas residen en la posibilidad de generar títulos de renta fija con la máxima calificación y una baja prima de riesgo, gracias a la estructuración de las emisiones en series diferenciadas de bonos, de forma que ciertas series absorben la mayoría del riesgo, facilitando que los tramos más seguros tengan una alta calificación. Se realiza una revisión de la literatura sobre los factores subyacentes a la generación de tramos y sobre los factores explicativos de la rentabilidad ofrecida por los bonos de titulización. Se concluye que la búsqueda de mercados más completos y la reducción de problemas asociados al riesgo moral, son los motivos principales para la estructuración multitramo. Dada la fuerte influencia del número de tramos sobre la rentabilidad ofrecida por las emisiones, se concluye que las estructuras multitramo han sido una herramienta eficaz para la colocación de bonos con rentabilidades muy competitivas.
Keywords: G12; G21; 650; Securitization; Primary yield; Tranche; Titulización; Rentabilidad primaria; Tramo